PERILAKU PENYALAHGUNAAN MINUMAN KERAS DI KALANGAN REMAJA DI DESA SULUAN KECAMATAN TOMBULU KABUPATEN MINAHASA - Mira Silvana Tampomalu; Ferdinand Kerebungu; A.R. Umaternate (Labor Program Studi Pendidikan Sosiologi, 2021)
The objectives to be achieved in this study are to examine the behavior of alcohol abuse and to describe the factors that influence adolescents to consume alcohol among adolescents in Suluan Village, Tombulu District. The focus of the research in this study is